Hak Atas Air Dalam Konstitusi Negara dan Pengelolaannya di Indonesia - Wiwik Harjanti (Fakultas Hukum Universitas Mulawarman, 2009)
Arrangement and protection for rights of water in constitution of the state become importance because water represent basic rights for all human being which is obliged to protected and fulfilled by state to its citizen. Form of the comittmen of state in arrangement and protection of rights of water can be seen from basic values in the arrangement of rights of the water in constitution, especially on Pasal 33 ayat (3) UUD NRI 1945 and also its management which arranged in UU Nomor 7 Tahun 2004 tentang Sumber Daya Air as implementation of UUD NRI 1945